The Effect of the Realistic Mathematics Education Approach on Improving the Arithmetic Operation Skills of Students with Intellectual Disabilities at the Junior High School Level - Hardiyanti, Hardiyanti; Mumpuniarti, Mumpuniarti (Journal of Educational Sciences, 2025)
The study aims to examine the effect of a Realistic Mathematics Education (RME) approach on improving arithmetic operation skills among students with intellectual disabilities. A quantitative method with a quasi-experimental design, specifically the One-Group Pretest Posttest Design, was employed, involving a pretest, an intervention, and a posttest. The participants consisted of 10 students at Bengalon 4 Junior High School who were identified as having intellectual disabilities. Data were collected through observations and standardised tests that experts had validated. The reliability scores were 0.731 for the pretest and 0.826 for the posttest. The data were analysed using both descriptive and inferential statistics, including normality testing and paired sample t-tests. The results show that the Realistic Mathematics Education approach significantly improves students’ arithmetic abilities. The average score increases from 46.00 to 72.50. Additionally, improvements are observed across numeracy indicators, although not evenly distributed. Full mastery is demonstrated on questions 1 and 2 (100% for all three indicators), while questions 3 and 4 show complete mastery of two indicators (100%).